A Cell-Line-Specific Atlas of PARP-Mediated Protein Asp/Glu-ADP-Ribosylation in Breast Cancer - Yuanli Zhen; Yajie Zhang; Yonghao Yu (Cell Reports, 2017)
PARP1 plays a critical role in regulating many biological processes linked to cellular stress responses. Although DNA strand breaks are potent stimuli of PARP1 enzymatic activity, the context-dependent mechanism regulating PARP1 activation and signaling is poorly understood. We performed global characterization of the PARP1-dependent, Asp/Glu-ADP-ribosylated proteome in a panel of cell lines originating from benign breast epithelial cells, as well as common subtypes of breast cancer. From these analyses, we identified 503 specific ADP-ribosylation sites on 322 proteins. Despite similar expression levels, PARP1 is differentially activated in these cell lines under genotoxic conditions, which generates signaling outputs with substantial heterogeneity. By comparing protein abundances and ADP-ribosylation levels, we could dissect cell-specific PARP1 targets that are driven by unique expression patterns versus cell-specific regulatory mechanisms of PARylation. Intriguingly, PARP1 modifies many proteins in a cell-specific manner, including those involved in transcriptional regulation, mRNA metabolism, and protein translation.